1995
DOI: 10.1139/f95-154
|View full text |Cite
|
Sign up to set email alerts
|

Population decline off the Japanese sardine Sardinops melanostictus owing to recruitment failures

Abstract: The Japanese sardine Sardinops melanostictus started to decline after 1989. Recruitment to age 1 population was small in four year-classes from 1988 to 1991. The population decline after 1989 resulted from recruitment failures in 4 consecutive years. Egg production was high in the years of poor recruitment. The recruitment failures were caused not by a reduction in reproductive output but by low survival between egg stage and age 1 recruitment. Abundance of post first-feeding larvae positively correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(97 citation statements)
references
References 8 publications
1
93
1
2
Order By: Relevance
“…The duration of the phase that is critical in controlling the growthrelated survival and in establishing the year-class strength has been considered to be about 90 d in Atlantic cod (Campana 1996) and about 1 yr in Japanese sardine Sardinops malanostictus (Watanabe et al 1995). Takasuka et al (2004) suggested that the roles of growth-related survival mechanisms in the recruitment dynamics could differ between pelagic fish species that undergo metamorphosis (with a gradual change in morphological, physiological, and ecological aspects) and those that settle through metamorphosis such as flatfishes.…”
Section: Timing Of Growth-selective Survival and Its Role In Determinmentioning
confidence: 99%
“…The duration of the phase that is critical in controlling the growthrelated survival and in establishing the year-class strength has been considered to be about 90 d in Atlantic cod (Campana 1996) and about 1 yr in Japanese sardine Sardinops malanostictus (Watanabe et al 1995). Takasuka et al (2004) suggested that the roles of growth-related survival mechanisms in the recruitment dynamics could differ between pelagic fish species that undergo metamorphosis (with a gradual change in morphological, physiological, and ecological aspects) and those that settle through metamorphosis such as flatfishes.…”
Section: Timing Of Growth-selective Survival and Its Role In Determinmentioning
confidence: 99%
“…The largest landing of sardine in Japan was 4.49 million tons in 1988; in contrast, the catch in recent years has been <1% of this amount. Watanabe et al (1995) attributed this drastic fluctuation in stock to large recruitment variability, especially with regards to the survival rate from the end of first-feeding larvae to age-1.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the larval stage is particularly sensitive to complete nutrient deprivation, as survival through metamorphosis determines the year-class strength (Watanabe and Kiron 1994;Watanabe et al 1995). In the current study, we investigated whether compromised nutritional status in white sturgeon larvae, during their early exogenous feeding phase, affects heat shock protein responses to thermal stress, which may subsequently affect larval survival.…”
Section: Introductionmentioning
confidence: 99%